Os programas metafísicos de investigação em Popper como berçário da ciência - Kuhn, William Carlos (2017)
This work aims the investigation of the relationship between metaphysics and science using the popperian concepts of metaphysical realism and the metaphysical research programs. The place of metaphysics was reevaluated throughout the developments of popperian philosophy and changed the situation of excluded from the domain of science, by its non-testability at first, to be incorporated directly into the scientific methodology at second. A cause for this is that Popper thought the methodology is not empirical, but possibly metaphysical and normative, besides the realism, while metaphysical in nature, and non-testable, is open to criticism. The philosopher thought the methodology of science saying that induction must be rejected as a characteristic method of science and replaced by falsifiability, whose assumption is that universal theories are accepted as conjectures, considering the fallibility of our knowledge. We see that Popper, in developing his falseationist theory of method he accepted the correspondential truth theory due to the understanding that it was the only well suited option to the falsifiability and its metaphysical realism and had no choice but admitting the problems arising as a mystery. Popper didn´t realize that in doing so he created problems for the rest of his own philosophy, especially for the thesis of knowledge as a human invention. Thus it seems that popperian realism and its presupposition of natural laws seems to have been sustained by the belief in the connection of this with the latent aim of science, which is in his point of view the search for truth. But it seems this conception of truth, as Caponi (1996) also pointed out, can be understood as an idealization of rational acceptance, which seems to be an acceptable internalist alternative as more compatible with falseasionism and, at the same time, as an outline of difficulties arising from the metaphysical commitments of popperian realism. We understand that the defense of realism for Popper is also motivated by the attempt to avoid one of the negative ethical consequences of solipsism that is the human suffering. At this point we see the metaphysical programs of investigation seemmingly occupying the function of the methodology in terms of their programmatic character. Therefore, the methodology will depend on a metaphysics. We see that a reasonable explanation for this shift in Popper's perspective of metaphysics is the understanding that criticism regulates both metaphysics and empirical science. Thus, the demarcation that makes sense at all is that between criticisms and non-criticism, that is, falsification is not a strict criterion make possible the idea about the influence of metaphysics in science. The predominance of criticism over knowledge allows imaginative theories such as some metaphysical programs to provide content-rich insights and contribute on problems selection and its interpretation. Criticism, therefore, is the link between metaphysics and science.